Synergizing Topic Modeling in Analyzing Media Discourse on China’s Dual-Carbon Commitment and Actions - Yuan Fan; Linda H. F. Lin (SAGE Open)
The media discourse surrounding climate change has evolved beyond issues of science and public health, becoming increasingly politicized and intertwined with broader ideological and geopolitical dynamics. While existing research has examined how Chinese state-run media constructs climate narratives, few studies have explored such discourse across national and ideological borders to understand how China’s dual-carbon commitment is discursively represented. To bridge this gap, this study examines news reports between September 22, 2020 and December 31, 2023 from three globally influential newspapers: People’s Daily (PD), the Guardian (TG), and the New York Times (NYT). Combining topic modeling and discourse-historical analysis, this study investigates both recurring themes and the discursive strategies employed to portray China’s dual-carbon commitment. Findings reveal that while all three newspapers highlighted multilateral cooperation, they differed significantly in framing China, its climate actions and responsibilities: PD emphasized China’s low-carbon achievements primarily through top-down narratives and framed its practice as aligned with global well-being, whereas TG and NYT underscored inconsistencies between China’s pledge and actions mainly through selective statistics and anecdotal critiques, reflecting distinct ideological and geopolitical standpoints. In addition to explicit strategies such as nomination and predication, this study has also identified patterns of “concealment” across the corpora, where certain issues were downplayed or omitted to influence public attitudes and perceptions in directions that support each outlet’s particular agenda and strategic interests. This study contributes to the field of environmental communication by illustrating how media discourse reflects and reinforces broader power relations, ideological divides, and national interests.